Gambaran Skrining Keterlibatan Penggunaan Alkohol, Rokok dan Zat Adiktif pada Mahasiswa D3 Fakultas Teknik Universitas Gadjah Mada - Dyah Esti Kurniawati, Sri Warsini, Carla Raymondalexas Marchira (Berita Kedokteran Masyarakat (BKM), 2010)
Background: A student is one group that is vulnerable to abuse alcohol, tobacco and addictive substances. The level of risk dependence on the use of alcohol, tobacco and addictive substances vary and can be identified through screening using the ASSIST.Objectives: To determine the involvement of the picture using alcohol, tobacco and addictive substances in the Faculty of Engineering students D3 UGM.Methods: This study is a descriptive type of research uses cross-sectional design. This study population was all students D3 UGM Faculty of Engineering who never use alcohol, tobacco and addictive substances during his lifetime. Respondent of the study are 86 students of the Faculty of Engineering D3 UGM batch 2008. Data was collected using  Alcohol, Smoking and Substance Involvement Test (ASSIST). Study was done  in August and September 2009.Results: The type of addictive substances consumed by the majority of students D3 UGM Faculty of Engineering are other addictive substances (88.37%), cigarettes (69.77%) and alcohol (29.07) whereas that is never consumed cocaine, amphetamine type stimulants , hallucinogens and opioids. All students D3 UGM Faculty of Engineering is using these addictive substances in the last 3 months.Conclusion: The level of use of tobacco dependence risk, inhalant, cannabis, sedatives and other addictive substances (coffee or tea) at the Faculty of Engineering students D3 UGM Force in 2008 the majority  of categories were, for the use of alcohol while the majority is in the low category.Keywords: screening, alcohol, cigarettes, addictive substances, students